Semiología de la identidad visual de las cooperativas de ahorro y crédito indígenas de Riobamba y su relación con el branding Corporativo - Castelo Guerrero, Steeven Alonso (2025)
This research analyzes the semiology of visual identity in Riobamba's indigenous savings and credit cooperatives and its relationship with corporate branding. The main objective is to determine how the graphic and symbolic elements used in these cooperatives' visual identities influence the perception of their members and the consolidation of their brand. For this, a qualitative study was carried out to analyze logos, colors, typographies, and other visual signs used by cooperatives, complemented by interviews and surveys aimed at members and experts in graphic design and corporate communication. The results show that these institutions' visual identities are based on cultural and community symbols that reinforce their roots with the indigenous population, promoting trust and a sense of belonging. However, inconsistencies were identified in the application of these elements, which may affect the effectiveness of your corporate branding. It is concluded that a well structured visual identity aligned with cooperative principles strengthens brand positioning and member loyalty. A more coherent and uniform branding strategy is recommended to optimize the communication and recognition of these cooperatives in the financial market.